Pemetaan Distribusi dan Densitas Monyet Hitam Sulawesi (Macaca Nigra) di Sulawesi Utara - Saroyo Saroyo; Roni Koneri (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
A study on mapping of distribution and population of Sulawesi crested black macaques (Macaca nigra) has been carried out to evaluate the current condition of distribution and density. This research was conducted from January to November 2009 at 24 locations in North Sulawesi Province. Determination of M. nigra distribution was based on the information provided by people surrounding the sites and field observation. Line transect was used to evaluate the density of the monkey with the length based on the habitat condition and the width was 100 m. The results showed that monkeys were not found at all of the locations and based on categories, high density of monkey was only found at Tangkoko-Batuangus Nature Reserve Two serious problems responsible to monkey population decreasing were hunting for consumption and habitat destruction. It can be concluded that distribution of M. nigra in North Sulawesi is meta-population and the current status of the species as critically endangered is accepted; the conservation of this species depends on the active management and terminating the factors of population decreasing.